Child developmental delay and its associated factors among children aged 12–59 months in Dembecha district, Northwest Ethiopia: a community-based cross-sectional study - Kerebh, Adugna; Endalifer, Melese Linger; Birhanu, Molla Yigzaw; Telayneh, Animut Takele; Abate, Lake Kumlachew; Adissie, Zemene; Negesse, Ayenew; Alamneh, Alehegn Aderaw (Frontiers in Public Health, 2024)
BackgroundDevelopmental delay is a group of disorders that cause common deficits of adaptive and intellectual function in children. It happens when a child fails to achieve one aspect of developmental skills. Limited information is available regarding the prevalence of developmental delay among children aged 12–59 months in the study area. Therefore, this study aimed to assess the prevalence of developmental delay and its associated factors among this population.MethodsA community-based cross-sectional study was conducted in Dembecha district among 702 children aged 12–59 months. Data were gathered through face-to-face interviews, and by taking anthropometric measurements using a pretested structured questionnaire. Data were entered into Epi Data version 4.2 software and exported into Statistical Package for Social Science (SPSS) version 25 software for analysis. The WHO Anthro software was used to analyze anthropometric-related data. Bivariable and multivariable binary logistic regression analyses were done to identify factors associated with developmental delay. The odds ratio with a 95% Confidence Interval (CI) was estimated to determine the strength of the association.ResultsThe prevalence of developmental delay among children was 26.7% (95% CI: 23.5, 30.2). Toddler child age (AOR = 2.60; 95% CI: 1.42, 4.87), low birth weight (LBW; AOR =4.90; 95% CI: 2.14, 11.48), cesarean section mode of delivery (AOR = 8.60; 95% CI: 3.93, 18.65), preterm delivery (AOR = 2.5; 95% CI: 1.28, 4.74), early initiation of complementary feeding (AOR = 8.40; 95% CI: 3.61, 19.63), stunting (AOR = 2.90; 95% CI: 1.67, 5.22) inadequate meal frequency (AOR = 3.20; 95% CI: 1.74, 5.94), and inadequate dietary diversity (AOR = 3.10; 95% CI: 1.68, 5.85) were significantly associated with child developmental delay.ConclusionThe prevalence of developmental delay among children was high in Dembecha district compared to the global prevalence. Child developmental delay was associated with toddler child age, LBW, cesarean section mode of delivery, preterm delivery, initiation of complementary feeding before 6 months, stunting, inadequate meal frequency, and inadequate dietary diversity. Therefore, preventing preterm delivery and LBW, initiating complementary feeding before 6 months, stunting, and achieving the minimum meal frequency, and minimum dietary diversity are recommended to prevent child developmental delay.